Acquisition of cardiovascular kinetics via treadmill exercise – A tool to monitor physical fitness during space missions. (September 2021) - Koschate, Jessica; Hoffmann, Uwe; Lysova, Nataliya; Thieschäfer, Lutz; Drescher, Uwe; Fomina, Elena
Abstract: Introduction: The aim of the preliminary presentation of results of the ongoing project onboard the International Space Station (ISS) is to evaluate whether the application of a kinetics test protocol with pseudo randomized changes of moderate walking speeds on a treadmill is feasible on board the ISS, and whether potential changes in cardiorespiratory parameters can be tracked. Methods: Overall, 5 male cosmonauts (47 ± 3 yrs) were tested before and after the space mission on a treadmill, applying pseudo randomized changes in speed until subjective exhaustion. Of these, 3 cosmonauts were also tested during space flight. Oxygen uptake (only pre/post) and heart rate (HR) were measured and time series analysis was used to obtain kinetics information. Higher maxima of the cross-correlation functions (CCFmax ) between the applied velocity and the respective parameter indicate faster kinetics. Results: Peak treadmill velocity (pre vs. post: 13.9 ± 1.7 vs. 12.4 ± 1.9 km/h; p = 0.043) was significantly slower after space flight. Average HR values during rest (69 ± 5 vs. 79 ± 10 beats/min, p = 0.043), 6 km/h (102 ± 14 vs. 113 ± 16 beats/min, p = 0.043) and 10 km/h (129 ± 9 vs. 138 ± 11 beats/min, p = 0.043) were higher, and HR kinetics (0.68 ± 0.08 vs. 0.44 ± 0.08, p = 0.043) were significantly slower after space flight. Discussion: The kinetics test with pseudo randomized, moderate work rate (WR) changes on a treadmill is applicable in the exercise test setting onboard the ISS. Cardiorespiratory kinetics were slowed after the long duration space flight, which provides important information about the underlying mechanisms of decreases in physical fitness. Highlights: Cardiorespiratory kinetics can be tested by randomized changes in treadmill speed onboard the ISS. Cardiorespiratory kinetics were slowed after long duration space flights. Measuring heart rate (HR) kinetics is important to track changes in aerobic fitness. HR kinetics can give important information for exercise training prescription. Critical values should be identified for HR kinetics.